Personalized Breast Cancer Prognosis through Data Mining Innovations - Dr.B Rama Ganesh, Praveen B M, Krishna Prasad K , Viswanath G (Cuestiones de Fisioterapia, 2024)
Progress in medical research on cancer diagnosis and prognosis, especially in breast cancer, has imposed considerable demands on oncologists due to the disease's complex and varied characteristics. Research aimed at estimating breast cancer survival has been proposed to tackle this difficulty.